Genetically engineered pH-responsive silk sericin nanospheres with efficient therapeutic effect on ulcerative colitis. (May 2022) - Xu, Sheng; Yang, Qianqian; Wang, Riyuan; Tian, Chi; Ji, Yanting; Tan, Huanhuan; Zhao, Ping; Kaplan, David L.; Wang, Feng; Xia, Qingyou
Abstract: Ulcerative colitis (UC) is one type of inflammatory bowel disease (IBD) and lactoferrin (LF) is a promising protein drug to treat UC. However, targeted LF delivery to optimize bioavailability, targeting and effectiveness remains a challenge. Here, we report an effective strategy to fabricate silk sericin nanospheres systems for the delivery of recombinant human lactoferrin (SS-NS-rhLF). The system is based on the use of optimized transgenic silkworms to generate genetically engineered silk fibers (rhLF-silks). The rhLF silks were used for fabricating SS-NS-rhLF by ethanol precipitation. The SS-NS-rhLF were stable with a spherical morphology with an average diameter of 123 nm. The negatively charged sericins in a pH ≥ 5.5 environment achieved specific targeting of the SS-NS-rhLF to positively charged colonic sites. The SS-NS-rhLF achieved efficient uptake by cells in the inflamed colon of mice when compared to free lactoferrin in solution (SOL-rhLF). Furthermore, oral administration of the SS-NS-rhLF with low dose of rhLF significantly relived symptoms of UC in mice and achieved comparable therapeutic effect to the high dose of SOL-rhLF by supporting the reformation of cell structure and length of colon tissue, reducing the release of inflammatory factors, inhibiting the activation of the NF-κB inflammatory pathway, and maintaining a stable intestinal microbial population in mice. These results showed that the SS-NS-rhLF is a promising system for colitis treatment. Statement of significance: Targeting and effective delivery of multiple biological functional protein human lactoferrin (rhLF) is a promising strategy to treat ulcerative colitis in the clinic. Here, rhLF-transgenic silk cocoons were used to fabricate a rhLF-sericin nanosphere delivery system (SS-NS-rhLF). The fabricated SS-NS-rhLF showed identical spherical morphology, stable structure, sustainable rhLF release, efficient cell uptake and negative charge in an environment of pH above 5.5, thus realized the specific targeting to the positively charged colonic sites to treat UC mice through oral administration. The therapeutic effect of SS-NS-rhLF with a low rhLF dose in the UC mice was comparable to the high dose of free rhLF treatment in solution form, suggesting that the SS-NS-rhLF is a promising system for colitis treatment. Graphical abstract: Image, graphical abstract